Design, synthesis, and in vitro antiplatelet aggregation activities of taiwanin C - Daron, Érika C. A. S. K. [UNESP] (2022)
Total synthesis of taiwanin C was realised efficiently in a global yield of 52%. Taiwanin C in aggregation assays inhibited platelet aggregation in a concentration-dependent manner with an IC50 of 0.46 μM after exposure of human platelet to AA. Similarly, to AA, taiwanin C inhibited significantly TRAP-6-induced platelet aggregation with IC50 of 0.56 μM. Molecular docking studies were carried out using the molecular target the COX-1, COX-2 and PAR-1 proteins. These studies suggest that taiwanin inhibits COX-1 more strongly than COX-2. Taiwanin C showed better antiplatelet action in the presence of TRAP-6 than indomethacin and molecular docking studies suggest different mechanisms of action for the two compounds on PAR-1. These results demonstrate that taiwanin C acts very efficiently in two different signaling pathways of platelet aggregation. Although preliminary, these results indicate that taiwanin C has potential for further studies on its use for the development of new antiplatelet.